Conhecimentos e dificuldades dos estudantes do ensino médio relacionados ao conjunto dos números reais - Bartolomeu, Vivaldo de Souza (2010)
The goal of this research is to examine the learning and difficulties of high school seniors students with the real numbers. For this, was made a diagnostic test with 54 students, with 18 from 1st year, 18 from 2nd year and 18 from 3rd year of high school seniors; everyone from State Public School System. This research has a qualitative approach, referenced by LUCKESI (2005) and his analyses show a blank between student learning and Mathematics knowledge, then is proposed a change on the methods to teach real numbers, according with DIAS (2002). The results revealed that most of the students are not familiar with this topic, although the Real number was taught at High School. It is necessary to review this teaching process with Real Numbers